Involvement of avirulence genes avrA and popP1 of Japanese Ralstonia solanacearum strains in the pathogenicity to tobacco. (April 2018) - Chen, Li; Dahal, Amol; Zhang, Yong; Rokunuzzaman, Md; Kiba, Akinori; Hikichi, Yasufumi; Ohnishi, Kouhei
Abstract: We investigated the involvement of two avirulence genes, avrA ( ripAA in unified nomenclature) and popP1 ( ripP1 in unified nomenclature), of Japanese Ralstonia solanacearum strains in the pathogenicity to tobacco. One virulent strain OE1-1 and four hypersensitive response (HR)-eliciting strains, 8107, MAFF 211471, MAFF 211496, and MAFF 301520, were used. While 8107 and MAFF 211471 contain popP1, other three strains do not. When popP1 of strain 8107 was transferred into the virulent strain OE1-1, the transconjugant strain had significantly reduced virulence but did not become a HR-eliciting strain. We deleted avrA and/or popP1 from the HR-eliciting strains; all deletion mutants still elicited a HR and did not become virulent to tobacco, although leaf lesion appearance was delayed on infection with avrA mutants. These results indicate that although avrA and popP1 could be functional as avirulence determinants, other unidentified factors are necessary for full virulence or HR elicitation by Japanese R. solanacearum strains. Highlights: RipAA and RipP1 areavirulence factors in Japanese R. solanacearum strains. Expression of RipP1 in a virulent strain greatly reduces pathogenicity to tobacco. ripAA ripP1 double deletion in HR-eliciting strain delays HR induction. Unknown effector in Japanese strains could be involved in HR induction on tobacco. HR-induction mechanism on tobacco is different among R. solanacearum strains.